PERKAWINAN USIA MUDA DAN PERCERAIAN DI KAMPUNG KOTABARU KECAMATAN PADANGRATU KABUPATEN LAMPUNG TENGAH - Nurhasanah, Umi; Susetyo, Susetyo (JURNAL SOSIOLOGI, 2013)
This study aims to identify and explain the cause of the occurrence of child marriage, problems that occur in housekeeping, and to explain the impact of child marriage on life in the village housekeeping Kotabaru Padangratu Central Lampung. This type of research is descriptive qualitative. by using the method of data collection are observation, namely the systematic observation and recording of the behavior by watching or observing individuals or groups directly. Interview, by asking a number of questions will be answered orally and verbally anyway. Data was collected through interviews and documentation. Further data analysis was performed with data reduction, display or presentation of the data and conclusions stage. The results showed that the cause of the couple to marriage at a young age is due to Kampung Kotabaru free sex, free sex increasingly widespread among teenagers due to the mengendornya social control in the community because of a shift in cultural values ada.selain because of economic factors, that marriage performed at a young age as an alternative to alleviate the economic burden of the family. Low educational factors make the perspective and mindset of adolescents are more narrow. And the encouragement of parents. which then have an impact lost educational opportunities, lost the opportunity to develop and express themselves, vulnerable to pregnancy and fetal problems, susceptible to domestic violence and child marriage could lead to social problems that can lead to divorce. Keywords: marriage, age youth, divorce